2017
DOI: 10.1210/en.2017-00405
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Steroid Receptor Coexpression and Circadian-Timed Activation of Kisspeptin and RFRP-3 Neurons May Contribute to the Sexually Dimorphic Basis of the LH Surge

Abstract: In rodents, the ovulation-inducing luteinizing hormone (LH) surge is sexually dimorphic, occurring only in females, but the reasons for this sex difference are unclear. Two neuropeptides, kisspeptin and RFamide-related peptide 3 (RFRP-3), are hypothesized to regulate the gonadotropin-releasing hormone (GnRH)/LH surge. In females, both of these systems show circadian changes coincident with the LH surge, but whether males show similar temporal changes under comparable hormonal conditions is unknown. Here, we ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 58 publications
3
31
0
Order By: Relevance
“…These injections led to a rapid, dose‐dependent suppression of LH, indicating a likely role in oestradiol negative‐feedback regulation. Additionally, our studies found that the removal of oestradiol negative‐feedback at the time of the LH surge is mediated, at least in part, via circadian‐controlled inhibition of the RFRP‐3 system, with analogous findings recently reported in mice . These studies showing coordinated suppression of RFRP‐3 cellular activity with pro‐oestrus were conducted in an oestrogen‐clamped LH surge model.…”
Section: Gnih/rfrp‐3 Control Of the Ovulatory Cycle And Female Reprodsupporting
confidence: 87%
See 1 more Smart Citation
“…These injections led to a rapid, dose‐dependent suppression of LH, indicating a likely role in oestradiol negative‐feedback regulation. Additionally, our studies found that the removal of oestradiol negative‐feedback at the time of the LH surge is mediated, at least in part, via circadian‐controlled inhibition of the RFRP‐3 system, with analogous findings recently reported in mice . These studies showing coordinated suppression of RFRP‐3 cellular activity with pro‐oestrus were conducted in an oestrogen‐clamped LH surge model.…”
Section: Gnih/rfrp‐3 Control Of the Ovulatory Cycle And Female Reprodsupporting
confidence: 87%
“…Additionally, our studies found that the removal of oestradiol negative-feedback at the time of the LH surge is mediated, at least in part, via circadian-controlled inhibition of the RFRP-3 system, 27 with analogous findings recently reported in mice. 69 These studies showing coordinated suppression of RFRP-3 cellular activity with pro-oestrus were conducted in an oestrogen-clamped LH surge model. However, RFRP-3 cellular activity is suppressed during pro-oestrus in naturally cycling hamsters as well.…”
Section: G Nih/rfrp -3 Control Of the Ov Ul Atory C Ycle And Femalementioning
confidence: 99%
“…Earlier work in female Syrian hamster reported a monosynaptic connection between the SCN and RFRP-3 neurons, suggesting that RFRP-3 neurons are regulated by the SCN clock (47). In accordance with this hypothesis, a daily rhythm in RFRP-3 neuronal activity has been reported, with a lower number of RFRP-3 neurons expressing c-FOS coincident with the timing of the LH surge in female Syrian hamsters (44, 47) and mice (101). Equivocal findings are reported regarding the association between RFRP-3 cell activation state and the number of Rfrp expressing neurons, with daily variation in RFRP-3 neuronal activity being associated (47) or not (44, 101), with corresponding changes in the number of Rfrp expressing cells.…”
Section: Rfrp-3 Contributes To the Daily Rhythm Of Reproduction In Fesupporting
confidence: 56%
“…Double-label ISH for cfos+Kiss1 and cfos+Rfrp were performed on an additional set of brain sections in order to assess neuronal activation. Both single- and double-label ISH assays were performed using well-published protocols and validated P33 or DIG-labeled riboprobes, as previously reported (Poling, et al 2017; Semaan and Kauffman 2015; Stephens, et al 2016; Stephens, et al 2017). After ISH slides were developed and coverslipped, a custom automated image processing and quantification software program (Dr. Don Clifton, University of Washington) was used to analyze ISH slides under computer-assisted microscopy, by an investigator blinded to treatment groups.…”
Section: Methodsmentioning
confidence: 99%